Could Milkability Parameters Serve as a Reliable Tool to Predict the Morphology of Teat Structures and Their Milking-Induced Changes? - Iveta Szencziová; Matúš Gašparík; Jaromír Ducháček; Eva Tóthová Tarová; Melinda Nagy; Luděk Stádník; Mária Mičiaková; Radim Codl (Animals)
The study aimed to explore if milkability parameters could reliably predict the dimensions of teat structures and their milking-induced changes. Ultrasonography repeatedly measured the teat structures of 48 Holstein cows from mid to late lactation. We found that milking-induced changes in each structure are affected by different milkability parameters. Regression models for teat canal change and length change were significant, and variability was found to be 46.03% and 21.50%, respectively. Similarly, the teat structure’s dimensions significantly affected milkability parameters, which differed for each structure. However, regression models only explained between 3.36% (teat length) and 7.59% (cistern) of variability. The prediction potential, performed based on milkability, is limited if the initial dimensions of structures are not provided. If teat dimensions were measured at the beginning of the production life, automatically collected milkability data could be used to calculate milking-induced changes incurred with each milking and the development of teat dimensions over the production life. If perfected, this tool could provide alerts about critical milking-induced changes and risky teat conformation traits, as they have a proven effect on udder health and are reliable indicators of milking effectiveness.